An Operando Mechanistic Evaluation of a Solar‐Rechargeable Sodium‐Ion Intercalation Battery. Issue 19 (3rd July 2017) - Lou, Shi Nee; Sharma, Neeraj; Goonetilleke, Damian; Saputera, Wibawa Hendra; Leoni, Thomas M.; Brockbank, Paul; Lim, Sean; Wang, Da‐Wei; Scott, Jason; Amal, Rose; Ng, Yun Hau
Abstract: Solar‐intercalation batteries, which are able to both harvest and store solar energy within the electrodes, are a promising technology for the more efficient utilization of intermittent solar radiation. However, there is a lack of understanding on how the light‐induced intercalation reaction occurs within the electrode host lattice. Here, an in operando synchrotron X‐ray diffraction methodology is introduced, which allows for real‐time visualization of the structural evolution process within a solar‐intercalation battery host electrode lattice. Coupled with ex situ material characterization, direct correlations between the structural evolution of MoO3 and the photo‐electrochemical responses of the solar‐intercalation batteries are established for the first time. MoO3 is found to transform, via a two‐phase reaction mechanism, initially into a sodium bronze phase, Na0.33 MoO3, followed by the formation of solid solutions, Na x MoO3 (0.33 < x < 1.1), on further photointercalation. Time‐resolved correlations with the measured voltages indicate that the two‐phase evolution reaction follows zeroth‐order kinetics. The insights achieved from this study can aid the development of more advanced photointercalation electrodes and solar batteries with greater performances. Abstract : This work establishes an in operando synchrotron X‐ray diffraction methodology that allows for real‐time visualization of the structural evolution process within a solar‐rechargeable intercalation battery electrode. Time‐resolved correlations with measured voltages enable the structural transformation reaction rates to be determined. The information derived can aid the development of more advanced photointercalation electrodes and solar batteries with greater performances.